2020
DOI: 10.1088/1741-4326/ab8858
|View full text |Cite
|
Sign up to set email alerts
|

Observation of non-local effects in ion transport channel in J-TEXT plasmas

Abstract: In cold pulse experiments in J-TEXT, the ion transport shows similar non-local response as the electron transport channel. Very fast ion temperatures decreases are observed in the edge, while the ion temperature in core promptly begin to rise after the injection of cold pulse. Moreover, the cutoff density is also found for the ion non-local effect. The experimental observed density fluctuation in a high frequency ranging from 500 kHz to 2 MHz is obviously reduced in the whole plasma region during non-local tra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 39 publications
(72 reference statements)
0
10
0
Order By: Relevance
“…Experiment with 'cold-pulse propagation (CPP)' is more common than with 'heat-pulse propagation' [26,27], as it can be triggered more easily with a simple gas or impurity injection in the edge region of the tokamak plasmas. The impurity injections by laser blow off of target materials [1][2][3] and by gas injection through supersonic molecular beam [4][5][6] led to a significant drop in the edge temperature along with an increase in the core temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Experiment with 'cold-pulse propagation (CPP)' is more common than with 'heat-pulse propagation' [26,27], as it can be triggered more easily with a simple gas or impurity injection in the edge region of the tokamak plasmas. The impurity injections by laser blow off of target materials [1][2][3] and by gas injection through supersonic molecular beam [4][5][6] led to a significant drop in the edge temperature along with an increase in the core temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Following the previous observation of non-local transport (NLT) in multiple transport channels (electron temperature, particle, and momentum) [53], recent J-TEXT experiments reveal that the ion transport channel shows a similar non-local response to the electron transport channel [54], owing to the improved temporal resolution of the ion temperature measurement to millisecond level. Very fast ion temperature decreases are observed in the edge, while the ion temperature in the core promptly begin to rise after injection of the cold pulse.…”
Section: Observation Of Non-local Effects In Ion Transport Channelmentioning
confidence: 68%
“…Typical of these is the well know experiment of Gentle et al [7], in which a rapid rise in core temperature is observed in response to edge cooling. Ongoing work continues the study of these "non-local phenomena" [8].…”
Section: Introductionmentioning
confidence: 88%
“…When the zonally averaged profiles ⟨T ⟩ and ⟨n⟩ exhibit no corrugations, as shown in figure 1, we set 8) and ( 9) are the evolution equations for vorticity. In equation (8), the second term on the R.H.S can be combined with the L.H.S., yielding a useful evolution equation for potential vorticity ( φ − ∆ φ). Equation (9) shows that zonal vorticity evolves according to Reynolds force, as expected.…”
Section: From Kinetics To Pv Dynamicsmentioning
confidence: 99%